“Chinos masones”. La logia Chee Kung Tong 致公堂 en México - Chong, José Luis (2015)
The arrival of Chinese immigrants to Mexico since the 1870s was promoted by business and government to address the high demand for labor, caused by heavy inversions in mining, railways and agriculture. However, when starting the Mexican Revolution, these workers were systematically attacked, their property was confiscated and, they were almost all deported. During the “anti-Chinese campaign” Masonic lodge Chee Kung Tong致公堂gave them protection and support, functioning with the same characteristics as the ancient secret societies in China.